2014
DOI: 10.4265/bio.19.99
|View full text |Cite
|
Sign up to set email alerts
|

Seed Disinfection Effect of Atmospheric Pressure Plasma and Low Pressure Plasma on Rhizoctonia solani

Abstract: Gas plasma generated and applied under two different systems, atmospheric pressure plasma and low pressure plasma, was used to investigate the inactivation efficacy on the seedborne pathogenic fungus, Rhizoctonia solani, which had been artificially introduced to brassicaceous seeds. Treatment with atmospheric plasma for 10 min markedly reduced the R. solani survival rate from 100% to 3% but delayed seed germination. The low pressure plasma treatment reduced the fungal survival rate from 83% to 1.7% after 10 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 7 publications
1
23
0
Order By: Relevance
“…Seven samples were subjected to low-pressure plasma treatment as described by Nishioka et al 2014 . About 2 g of each sample were placed on the mesh sheet between electrodes in the plasma discharge chamber Fig.1 .…”
Section: Falling Microorganismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven samples were subjected to low-pressure plasma treatment as described by Nishioka et al 2014 . About 2 g of each sample were placed on the mesh sheet between electrodes in the plasma discharge chamber Fig.1 .…”
Section: Falling Microorganismsmentioning
confidence: 99%
“…Commensal organisms, which are originally found in plants, may survive the drying process and contribute towards the rise of food-borne illnesses Hashem and Alamri, 2010 . The warm and humid conditions in which they are grown favor the tion as an alternative method in medical instrument sterilization, and in recent times its application has spread to agriculture Nishioka et al, 2014 . The method involves the discharge of plasma, distributing gas in combination with ions, electrons and radicals, which inactivate the organisms upon interaction von Keudell et al, 2010 .…”
Section: Introductionmentioning
confidence: 99%
“…Our previous report Nishioka et al, 2014 indicated that the low-pressure plasma treatment under the same conditions as this study did not have significant negative effects on germination rates of brassicaceous seeds B. campestris var. amplexicaulis , and other studies have reported that plasma treatment of seeds improves their germination and sprouting process Bormashenko et al, 2012;Dhayal et al, 2006 . In this study, it was found that low-pressure plasma treatment could inactivate the important seed-borne plant pathogenic bacterium, X. campestris on seeds and damaged the bacterial cell membrane and biomolecules, such as DNA, inside the cells.…”
Section: Food Security Nato Sicence For Peace and Security Seriesmentioning
confidence: 99%
“…In a previous study Nishioka et al, 2014 , we measured the temperature around the mesh sheet in the plasma apparatus with a temperature indicator, and it was found that the temperature of the low-pressure plasma apparatus went up to 77 within 40 min. To distinguish the inactivation effect of the accompanying heat or ozone from that of the plasma, the heat studies described in the sections below were performed.…”
Section: Dry Heat Effect and Ozone Density During Plasma Treatmentmentioning
confidence: 99%
See 1 more Smart Citation